An Analysis Of Code Mixing Used By Ganjar Pranowo On Boy William’s Youtube Channel - Wahyudiantari, Ni Wayan Prami (JUPE : Jurnal Pendidikan Mandala, 2023)
Mixing one language with the other languages, in sociolinguistics field it called by code mixing. The use of code mixing in society it has been common. Code-mixing is part of the study of bilingualism in Sociolinguistics which have become a very popular language, it is to be an influence for smooth communication in Indonesia. It is thus necessary to study for smooth communication and prevent misunderstandings between speakers and hearers. This research aims analyzed the code mixing by Ganjar Pranowo on Boy William’s video YouTube channel. The objective of this research was to find out the types of code mixing by Ganjar Pranowo on Boy William’s video YouTube channel. This research was qualitative research design. In collecting the data, this research utilized documentation method. This study employed content analysis which focused on analyzing the types of code mixing which defined by Hoffman. The result after analyzing the video, there were forty data in the types of code mixing. In the types of code mixing,